Advances in Spatial and Temporal Databases: 14th International Symposium, SSTD 2015, Hong Kong, China, August 26-28, 2015. Proceedings - Claramunt, Christophe; Schneider, Markus; Wong, Raymond Chi-Wing; Xiong, Li; Loh, Woong-Kee; Shahabi, Cyrus; Li, Ki-Joune (LNCS sublibrary. SL 3, Information systems and applications, incl. Internet/Web, and HCI, 2015)
This book constitutes the refereed proceedings of the 14th International Symposium on Spatial and Temporal Databases, SSTD 2015, held in Hong Kong, China, in August 2015.The 24 revised full papers together with 8 demos presented were carefully reviewed and selected from 64 submissions. The conference program has the scope on following subjects: reachability query and path query, reverse query and indexing, navigation and routing, trajectory analysis, spatio-temporal approaches, privacy and matching, similarity search and pattern, keyword and pattern.